Gerak Mimesis Pada Penciptaan Tari Baruak Di Laban Kabupaten Pesisir Selatan Provinsi Sumatera Barat - Mentari Varianda; Gangga Lawranta (Dance and Theatre Review, 2026)
Mimesis Movement in the Baruak Dance of Laban, West Sumatera: A Manifestation Study. Baruak Dance is a traditional dance that lives and develops in Kampung Laban, Pesisir Selatan Regency, West Sumatra Province. This dance is inspired by the behavior of the Baruak (long-tailed macaque), which has a close relationship with the coastal community, particularly in daily life and economic activities. The emergence of Baruak Dance originates from the artist’s observation of the movements and behavior of the Baruak, which are subsequently processed and developed into a dance performance. This study aims to discuss Baruak Dance as a manifestation of mimetic movement, with particular emphasis on dance form and dancers’ expression. The research employs a descriptiveanalytical method with a qualitative approach, conducted through observations of movement patterns, performance structure, musical accompaniment, and dancers’ expressions. The results show that the movements in Baruak Dance represent imitations of Baruak behavior that have undergone processes of stylization and artistic transformation. The mimetic movements, characterized by their comical and communicative nature, constitute the main elements shaping the dance’s character and reflect the relationship between humans, nature, and the cultural values of the Pesisir Selatan community.Keywords: Baruak Dance, mimesis, traditional dance, Minangkabau